2014
DOI: 10.1002/2014ja019950
|View full text |Cite
|
Sign up to set email alerts
|

The solar type II radio bursts of 7 March 2012: Detailed simulation analyses

Abstract: Type II solar radio bursts are often indicators for impending space weather events at Earth.They are consequences of shock waves driven by coronal mass ejections (CMEs) that move outward from the Sun. We simulate such type II radio bursts by combining elaborate three-dimensional (3-D) magnetohydrodynamic (MHD) predictions of realistic CMEs near the Sun with an analytic kinetic radiation theory developed recently. The simulation approach includes the reconstruction of initial solar magnetic fields, the dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 72 publications
0
21
0
Order By: Relevance
“…Evidence for nonlinear currents at 2 f p is found in all 11 events, so antenna mechanisms may generate some of the observed radio emission. However, the recent simulation analyses of Schmidt and Cairns [] and Schmidt et al [], which include electrostatic decay, electromagnetic decay, and coalesence but not antenna mechanisms, predict well the dynamic spectra of some specific type II bursts in the range 1–14 MHz. This suggests that antenna mechanisms are less likely to be important for the present type II burst.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Evidence for nonlinear currents at 2 f p is found in all 11 events, so antenna mechanisms may generate some of the observed radio emission. However, the recent simulation analyses of Schmidt and Cairns [] and Schmidt et al [], which include electrostatic decay, electromagnetic decay, and coalesence but not antenna mechanisms, predict well the dynamic spectra of some specific type II bursts in the range 1–14 MHz. This suggests that antenna mechanisms are less likely to be important for the present type II burst.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we calculate the conversion efficiencies for fundamental and harmonic radio emission, φ F and φ H , respectively, for electromagnetic decay and Langmuir coalescence. We calculate φ F and φ H using equations (6)–(9) of Robinson and Cairns [], as in current theories for type II bursts [ Knock et al , ; Schmidt and Cairns , , , ; Schmidt et al , ], for the observed solar wind conditions, and v b =0.025 c . For the parameters that we cannot measure we assume typical values for the solar wind at 1 AU.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible scenario to account for the metric type II event and the EUV and WL observations of the CME shock is that, if both were due to the same shock, radio emissions were produced at the portions of the shock moving at low altitudes. Intense radio emission from a shock is enhanced when the shock is strong, fast, perpendicular, with large magnetic field compression ratios, and propagates into dense regions, favoring then the mirroring and acceleration of the lowenergy electrons that eventually generate the radio emission (e.g., Knock et al 2003;Feng et al 2013;Schmidt et al 2014). Quasi-perpendicular shock configurations were more likely to be found on the portions of the shock propagating at low altitude, and when the shock is traveling through high-density regions, such as coronal streamers, resulting in high-frequency metric type II radio emission.…”
Section: Coronal Shock Identificationmentioning
confidence: 99%